Into the Red: The Birth of the Credit Card Market in Postcommunist Russia - Аля Гусева (Journal of Economic Sociology, 2011)
The book “Into the Red: The Birth of the Credit Card Market in Postcommunist Russia” by Alya Guseva explores the emergence of the credit card industry in Russia and discusses the demand creation process for absolutely new product. The research is based both on the written sources and on interviews and archival data collected in two series in Moscow (Russia) from 1998 to 1999 and from 2003 to 2005. The author finds out that the socialist legacies shaped the Russian credit card market development. This path-dependence of the Russian market resulted in non-trivial solutions discovered by the market actors trying to cope with uncertainty and complementarity as two critical factors. Social networks play a vital role here as well. Networks joined by consumers and organizations aid to develop markets for mass consumption.The journal “Economic Sociology” publishes the first chapter of the book, “The Architecture of Credit Card Market”, providing with the theoretical foundations for the empirical research. This chapter addresses the problems faced by banks in nascent credit card market. Banks are expected to cope with uncertainty in credit lending, to create consumer demand and at the same time to appeal to merchants. In addition, there is a specific problem generated from cultural factors, including a mistrust of formal institution of money lending. The author briefly considers how the US banks and their Russian counterparts coped with the mentioned challenges.